PENGEMBANGAN MEDIA BUKU KOMIK BERBASIS MASALAH DALAM MATA PELAJARAN IPA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA KELAS IV SD - Setiawan, Bramianto; Siti Sofiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the lack of interesting teaching materials in elementary schools to improve students' problem-solving skills in the classroom. The purpose of this research is to produce problem-based comic products in Science Subjects in grade IV, which later learning in the classroom will be much more meaningful and fun, and can also improve students' ability to solve problems in learning. This study uses a type of development research using the ADDIE model. The instruments used for data collection are in the form of validation questionnaires, response questionnaires and post-test pre-tests to students. The results of this study resulted in Problem-Based Comics products that met the criteria very well with an average score of 87% from the three experts, namely 87% in the category of very suitable for use, and the level of practicality of 96% was in the criteria of very practical and the level of effectiveness with an average of 73% in the effective category. Problem-based comic teaching materials are feasible, practical and effective to be used in science learning material in the form of physical substances in grade IV elementary school.